Instrumentação básica e sistema de telemetria para baja - Pelisson, Angelo Abdallah (2018)
This work presents the development of a basic instrumentation and telemetry system for Baja, which is an off-road vehicle, in order to implement radio frequency data communication between the car and a computer and write this data to a flash memory. It is a project that aims to improve the performance of ProcoBaja Team in competitions, improving the existing electronics in the vehicle.